Professional Action Competence in Education for Sustainability Among Pre-service Physical Education Teachers: A Mixed Method Approach - Valérian Cece; Thomas Royet; Olivier Vors; Vanessa Lentillon-Kaestner (Current Issues in Sport Science)
Education for sustainability (EfS) represents a complex question that appears to require a holistic and emancipatory vision to achieve its long-term objectives. The action competence model for EfS aligns with this vision by considering both self-efficacy, knowledge, and willingness. Physical education (PE) offers a unique opportunity to implement EfS through the action competence model. This approach emphases the bodily dimension, learning through action, and affective and sensory aspects. However, EfS is not currently implemented in PE yet. It is therefore important to investigate the professional action competence of future PE teachers to identify potential barriers to implementing EfS in PE. A mixed-methods approach appears to be the most suitable for accurately assessing Professional Action Competence in Education for Sustainability.